The effects of greywater irrigation on vegetable crops and soil - Mzini, Loyiso Lloyd (Department of Environmental and Geographical Science, 2014)
Research on greywater irrigation has mainly focused attention on the reuse of greywater in relation to its quality and crop biomass but not on quality of edible vegetable crops. Thus a field experiment was established at the Umtata Dam Research Station where combinations of cabbages and onions; spinaches and beetroots; and carrots and lettuce were planted in to coincide with four different planting seasons (from October 2009 to December 2010). Crops were irrigated with greywater generated from bathing and dishwashing. Greywater was collected from a number of households in the vicinity of the Umtata Dam, in the Eastern Cape Province of South Africa. In the field experiment, vegetables were planted in three plots of the same composition of soil properties and then drip irrigated separately either with greywater, potable water, or with diluted greywater at a ratio of 1:1. The greywater quality, yield, aesthetical appeal, plant chemical analysis and soil chemical analysis were measured. Irrigation from diluted greywater showed a significant increase in yield, in the head mass and in appeal of cabbages. Onion yields were significantly higher when irrigated with greywater. Spinach also obtained significantly higher yields when irrigated with greywater, however many leaves from this treatment were infested with leaf-spot disease. Beetroot yield and quality was not affected with greywater irrigation, instead yield was reduced by 47% (4.686 tons/ha). Carrots did not show any significant difference in yield and root girth, but carrots irrigated with potable water were more appealing and longer in length. Lettuce irrigated with dilute greywater was significantly more appealing than other treatments. Sodium (Na) ions were elevated in cabbage, onions and were significantly higher in the case of lettuce and carrots when irrigated with greywater. Crude protein (CP) was observed to be significantly elevated on cabbages and lettuce when irrigated with diluted greywater whereas CP of onions and carrots were significantly lower due greywater irrigation. Significant increases in iron (Fe) were observed on cabbages and spinach when irrigated with diluted greywater, whereas lettuce Fe content was significantly elevated by greywater irrigation. There was no significant difference in cadmium (Cd) caused by irrigating spinach and lettuce with greywater, also those heavy metals that were significantly higher, were within the accepted threshold leaving the conclusion that lower levels of heavy metals posed no health risks to humans. In conclusion, greywater used in this study does not appear to cause an accumulation of salts and heavy metals in plants and soil, which suggests in this instance, that greywater does not pose a threat to plants and soils.